The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3758/s13415-016-0436-1
|View full text |Cite
|
Sign up to set email alerts
|

Basic psychological needs and neurophysiological responsiveness to decisional conflict: an event-related potential study of integrative self processes

Abstract: Fulfillment of the basic psychological needs for competence, relatedness, and autonomy is believed to facilitate people's integrative tendencies to process psychological conflicts and develop a coherent sense of self. The present study therefore used event-related potentials (ERPs) to examine the relation between need fulfillment and the amplitude of conflict negativity (CN), a neurophysiological measure of conflict during personal decision making. Participants completed a decision-making task in which they ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
5
19
0
Order By: Relevance
“…In fact, the integrative process central to SDT can itself be studied at a neurological level, including how it is optimized by basic need supports. Work by Di Domenico and colleagues (Di Domenico, Fournier, Ayaz, & Ruocco, ; Di Domenico, Le, Liu, Ayaz, & Fournier, ) shows how persons reporting greater basic need satisfaction have greater access to self‐relevant information, allowing better decision‐making when faced with difficult choices, a process mediated by the medial prefrontal cortex. More recently, Di Domenico et al () showed greater medial prefrontal cortex activation in people higher in basic need satisfaction when accessing past memories or future projections of self, again suggesting that need satisfaction conduces to more ready access to self‐representations across time.…”
Section: Neurological Basis Of Sdtmentioning
confidence: 99%
“…In fact, the integrative process central to SDT can itself be studied at a neurological level, including how it is optimized by basic need supports. Work by Di Domenico and colleagues (Di Domenico, Fournier, Ayaz, & Ruocco, ; Di Domenico, Le, Liu, Ayaz, & Fournier, ) shows how persons reporting greater basic need satisfaction have greater access to self‐relevant information, allowing better decision‐making when faced with difficult choices, a process mediated by the medial prefrontal cortex. More recently, Di Domenico et al () showed greater medial prefrontal cortex activation in people higher in basic need satisfaction when accessing past memories or future projections of self, again suggesting that need satisfaction conduces to more ready access to self‐representations across time.…”
Section: Neurological Basis Of Sdtmentioning
confidence: 99%
“…Participants were more undecided and less pleased when they decided between options of equal value compared to decision scenarios in which one option clearly outperformed the other. Moreover, the amplitude of the CN, a negative-going ERP that is thought to represent decision conflict in the medial prefrontal cortex (Di Domenico et al, 2016), was more negative on conflicting decisions relative to non-conflicting decisions. Regarding the monetary value of decision options, behavioural reactions became even stronger when more money was at stake: Participants were even more undecided and also slower in decisions when they deliberated between conflicting options of high monetary value.…”
Section: Discussionmentioning
confidence: 95%
“…Findings from recent neurophysiological studies suggest that self-determination entails a flexible and adaptive situation-specific attunement of approach and avoidance tendencies. Specifically, basic psychological need fulfillment-which includes the experience of self-determination-has been associated both with enhanced medial prefrontal activation (indicative of self-reflection) during the resolution of decisional conflicts (Di Domenico, Fournier, Ayaz, & Ruocco, 2013) and with enhanced anterior cingulate activity (indicative of behavioral inhibition) during the processing of avoidance goals (Di Domenico, Le, & Fournier, 2014). Furthermore, a motivational orientation toward self-determination has been associated with enhanced neuroaffective responsiveness to self-regulatory errors during response inhibition tasks (Legault & Inzlicht, 2013).…”
Section: Discussionmentioning
confidence: 99%